Selective Targeting and Tissue Penetration to the Retina by a Systemically Administered Vascular Homing Peptide in Oxygen Induced Retinopathy (OIR) - Maria Vähätupa (MDPI AG, 2021)
Pathological angiogenesis is the hallmark of ischemic retinal diseases among them retinopathy of prematurity (ROP) and proliferative diabetic retinopathy (PDR). Oxygen-induced retinopathy (OIR) is a pure hypoxia-driven angiogenesis model and a widely used model for ischemic retinopathies. We explored whether the vascular homing peptide CAR (CARSKNKDC) which recognizes angiogenic blood vessels can be used to target the retina in OIR. We were able to demonstrate that the systemically administered CAR vascular homing peptide homed selectively to the preretinal neovessels in OIR. As a cell and tissue-penetrating peptide, CAR also penetrated into the retina. Hyperoxia used to induce OIR in the retina also causes bronchopulmonary dysplasia in the lungs. We showed that the CAR peptide is not targeted to the lungs in normal mice but is targeted to the lungs after hyperoxia-/hypoxia-treatment of the animals. The site-specific delivery of the CAR peptide to the pathologic retinal vasculature and the penetration of the retinal tissue may offer new opportunities for treating retinopathies more selectively and with less side effects.